2013
DOI: 10.1007/978-1-4614-7209-4_2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Peptides by Denaturing Ultrafiltration and LC-MALDI-TOF-MS

Abstract: The dynamic range of complex biological samples represents a challenge for mass spectrometric characterization. Removal of high abundant proteins is a prerequisite for a successful mass spectrometric analysis of low abundant analytes. In particular, plasma and serum proteome span at least ten orders of magnitude and represent a major challenge for biomarker discovery. Immunoaffinity depletion is the most common methods of removal of high abundant proteins. Here we describe coupling of denaturing ultrafiltratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The advantages of different methods have previously been compared for peptide recovery . The most used peptide enrichment method is centrifugal ultrafiltration, which uses molecular weight cutoff (MWCO) membranes to separate low and high molecular weight peptides . This method is fast, easy to perform and can identify many unique peptides in serum and plasma. , However, peptides with molecular weights close to the cutoff point may be lost, such as apolipoproteins, and some “sticky” lipophilic peptides might be lost by binding to the membranes.…”
Section: Methodologies For Peptidomics Analysismentioning
confidence: 99%
“…The advantages of different methods have previously been compared for peptide recovery . The most used peptide enrichment method is centrifugal ultrafiltration, which uses molecular weight cutoff (MWCO) membranes to separate low and high molecular weight peptides . This method is fast, easy to perform and can identify many unique peptides in serum and plasma. , However, peptides with molecular weights close to the cutoff point may be lost, such as apolipoproteins, and some “sticky” lipophilic peptides might be lost by binding to the membranes.…”
Section: Methodologies For Peptidomics Analysismentioning
confidence: 99%
“…As an alternative approach, the fact that the majority of the high abundance proteins in serum are of comparatively high molecular weight has been used as a characteristic upon which to base a depletion protocol. Ultrafi ltration of serum with fi lters with molecular weight cut-offs of 50 and 30 kDa has been applied as a methodology in order to allow for the study of low abundance proteins/peptides [ 3 ]. Such protocols commonly dilute the serum with acidic solutions (2 % trifl uoroacetic acid for example) in order to dissociate peptides and proteins bound to albumin.…”
Section: Sample Preparation For Protein/peptides For Protein Profi Lingmentioning
confidence: 99%
“…Another study reported a method that coupled denaturing ultrafiltration with reverse phase fractionation and MS for characterization of low‐molecular‐weight proteins and peptides in serum and plasma samples . The enriched peptides were analyzed by RP‐LC combined with MALDI‐MS/MS characterization of the analytes, resulting in identification of 250 native peptides from 50 different proteins .…”
Section: Biomarker Discoverymentioning
confidence: 99%